2012
DOI: 10.6002/ect.2012.0128
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume as a Potential Predictor of Renovascular Thrombosis After Renal Transplant

Abstract: artIClE AbstractObjectives: We sought to evaluate the importance of mean platelet volume as a marker to follow-up, the tendency for hemorrhagic diatheses, and/or thrombotic complications in patients before and after renal transplant. Materials and Methods: Thirty-four patients (aged, 5 to 18 y) were included. Demographics of the patients, cause of chronic renal failure, dialysis modality, duration of dialysis, arterio-venous fistula thrombosis, and posttransplant immunosuppressive regimens were recorded and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…Recent studies were shown a significant negative correlation between platelet count and MPV in chronic illness. 6,7 Thrombocytosis associated with low level -but in normal range -of MPV has been shown in diseases such as inflammatory bowel disease, ulcerative colitis, rheumatoid arthritis and ankylosing spondylitis and these findings is more prominent in the active period of the disease. This finding can be used as an indicator of the disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies were shown a significant negative correlation between platelet count and MPV in chronic illness. 6,7 Thrombocytosis associated with low level -but in normal range -of MPV has been shown in diseases such as inflammatory bowel disease, ulcerative colitis, rheumatoid arthritis and ankylosing spondylitis and these findings is more prominent in the active period of the disease. This finding can be used as an indicator of the disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet morphology and size distribution were established as important factors affecting endothelial integrity in patients with coronary heart disease [11][12][13][14][15]. Importantly, correlation between platelet morphology and renal failure was reported in glomerulonephritis and postrenal transplantation [16][17][18]. It was also noticed that mean platelet volume (MPV) could serve as a marker of renal dysfunction in patients with stable angina [19].…”
Section: Introductionmentioning
confidence: 99%
“…1 This study showed that platelet numbers increased, and mean platelet volume levels decreased, after a pediatric renal transplant. However, I want to make a minor criticism of this study: In the Methods section, the authors failed to mention the time between sample collection and laboratory analysis.…”
mentioning
confidence: 90%